Dexmedetomidine versus Dexamethasone as Perineural Adjuvants in Supraclavicular Brachial Plexus Block: An Interventional Study - Charmi Hitenbhai Shah; Jinesh Pareshbhai Kothari; Nilesh Vrajmohan Shah; Rajsi Rajan Shah; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Supraclavicular block is a common regional anaesthetic technique for upper limb surgeries. Adjuvants like dexamethasone and dexmedetomidine can enhance the block’s efficacy and prolong the duration of anaesthesia and analgesia. Aim: To compare the effects of perineural dexamethasone versus perineural dexmedetomidine added to a local anaesthetic mixture in supraclavicular brachial plexus block for upper limb surgeries. Materials and Methods: This interventional study was conducted in the Department of Anaesthesiology at Dhiraj Hospital, Vadodara, Gujarat, India from October 2023 to April 2024 on 80 patients with American Society of Anaesthesiologists (ASA) physical status I and II, aged 18 to 65 years, scheduled for surgery under supraclavicular brachial plexus block. Patients were allocated into two groups of 40 patients each. Group 1 received 12 mL of 0.2% lignocaine with adrenaline and 13 mL of 0.5% bupivacaine along with dexmedetomidine 50 mcg. Group 2 received the same local anaesthetic mixture with dexamethasone 8 mg (2 mL). The onset and duration of sensory and motor blocks, haemodynamic changes {variations in pulse, blood pressure, and oxygen saturation (SpO2)}, duration of rescue analgesia, side-effects, and complications were evaluated. Chi-square test and t-test were applied for statistical evaluation. Results: Group 1 had a significantly lower average age (35.38±9.03 years) compared to Group 2 (46.40±13.12 years) (p=0.000039). Group 1 had a slower onset of sensory and motor blockade compared to Group 2 (14.38±2.19 minutes vs. 13.00±1.89 minutes, p=0.0036; 16.20±2.14 minutes vs. 15.70±1.99 minutes). Group 2 also showed significantly longer durations for motor blockade (918.75±65.80 minutes vs. 632.60±23.09 minutes, p=3.10×10-44), postoperative analgesia (1051.00±90.18 minutes vs. 811.12±17.23 minutes, p=1.00×10-28), and time for rescue analgesia (1116.75±93.96 minutes vs. 826.50±13.92 minutes, p=2.40×10-32). Haemodynamics and SpO2 were comparable between the two groups. Conclusion: Dexamethasone, as an adjuvant to a local anaesthetic mixture in supraclavicular brachial plexus block, provided excellent quality of postoperative analgesia with minimal side-effects. However, the incidence of hypotension and bradycardia was higher with dexmedetomidine, which could be managed with routine clinical measures.